Pragmatic person centred care - Sanjay Kalra; Suneet Kumar Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
This conceptual paper defines and describes pragmatic person centred care as an enhanced and expanded version of the construct of person centred care (PCC). Pragmatic person centred care is defined as health care that is respectful of, and responsive to the person’s preferences, needs and values, while being reflective of available resource, reserves, and restrictions, regulating and balancing all aspects and facets of care in a rational, realistic and renewable manner, so as to ensure optimal relief and results. Pragmatic person centred care is dependent upon four ‘pillars’: the person and their care givers, the public and peers, the health care profession and their ecosystem, as well as policymakers and planners. This comprehensive description makes the practice of PCC acceptable, practical and efficient. This concept should be integrated in all health care services, including primary care. Keywords: Chronic disease, community health, diabetes patient centred, person centred, psychosocial aspects